Milkweed plants bought at nurseries may expose monarch caterpillars to harmful pesticide residues. (September 2022) - Halsch, Christopher A.; Hoyle, Sarah M.; Code, Aimee; Fordyce, James A.; Forister, Matthew L.
Abstract: The decline of monarch butterflies in both the eastern and western United States has garnered widespread public interest. Planting milkweeds, their larval host plants, has been promoted as one action individuals can take, but little is known with respect to potential pesticide contamination of store-bought milkweeds. In this study, we collected leaf samples from 235 milkweed plants purchased at 33 retail nurseries across the US to screen for pesticides. Across all samples, we detected 61 different pesticides with an average of 12.2 (±5.0) compounds per plant. While only 9 of these compounds have been experimentally tested on monarch caterpillars, 38 % of samples contained a pesticide above a concentration shown to have a sub-lethal effect for monarchs. We detected only a modest predictive ability of retailer size and milkweed species; and plants with labels advertising their value for wildlife did not have fewer pesticides at concentrations known to have a negative effect on monarchs. These results demonstrate the extensiveness of pesticide exposure within nursery milkweeds and the potential impacts on monarchs and other insects exposed to store-bought plants. Highlights: Milkweeds were collected from stores in the United States and screened for pesticides. We detected multiple pesticides in every milkweed plant sampled. Over one third of samples contained a pesticide at a known harmful concentration for monarchs. Plants labeled as wildlife-friendly did not have fewer potentially harmful compounds.